45.6k views
1 vote
Solve for a.
a = 0
a = -1
a = 1
none

Solve for a. a = 0 a = -1 a = 1 none-example-1
User Ford Guo
by
6.1k points

1 Answer

4 votes

Answer:

None.

Explanation:

5/a - 2 / (1 - a) = 2 (a - 1)

Multiply each term by a(1 - a)(a - 1):

5 (1 - a)(a - 1) - 2a(a - 1) = 2a(1 - a)

5( a - 1 - a^2 + a) - 2a^2 + 2a = 2a - 2a^2

5(-a^2 + 2a - 1) - 2a^2 + 2a = 2a - 2a^2

-5a^2 + 10a - 5 - 2a^2 + 2a - 2a + 2a^2 = 0

-5a^2 + 10a - 5 = 0

-5(a^2 - 2a + 1) = 0

= -5(a - 1)^2 = 0

So a = 1.

But a = 1 cannot be a root because 2/ 1 - a would be 2/0 which is undefined.

Also 2 / (a - 1) is undefined.

User Maxhungry
by
6.9k points